2020
DOI: 10.21203/rs.3.rs-37132/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serology surveillance of anti-SARS-CoV-2 antibodies among asymptomatic healthcare workers in Malaysian healthcare facilities designated for COVID-19 care

Abstract: IntroductionHealthcare workers (HCW) are presumed to be at increased risk of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection due to occupational exposure to infected patients. We aim to determine the prevalence of anti-SARS-CoV-2 antibodies among asymptomatic HCW.MethodsWe prospectively recruited HCW from the National Public Health Laboratory and two COVID-19 designated public hospitals in Klang Valley, Malaysia between April 13th and May 12th, 2020. Quota sampling was applied to ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Several studies have reported 0–17.4% COVID‐19 prevalence among HCWs 2–14 . However, very few have evaluated the impact of COVID‐19 on specific medical departments 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported 0–17.4% COVID‐19 prevalence among HCWs 2–14 . However, very few have evaluated the impact of COVID‐19 on specific medical departments 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported 0-17.4% COVID-19 prevalence among HCWs. [2][3][4][5][6][7][8][9][10][11][12][13][14] However, very few have evaluated the impact of COVID-19 on specific medical departments. 17,18 Repici et al, in a multicenter study from Italy, reported a very low risk of COVID-19 among HCWs in the gastrointestinal endoscopy units.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations